Research workshop to research work: initial steps in establishing health research systems on Malaita, Solomon Islands - Kekuabata Esau; Harrington Humpress; Asugeni Rowena; Muse Alwin; Solomon Janella; MacLaren David J; Redman-MacLaren Michelle L; Speare Richard; Clough Alan R (BMC, 2010)
Abstract Introduction Atoifi Adventist Hospital is a 90 bed general hospital in East Kwaio, Malaita, Solomon Islands providing services to the population of subsistence villagers of the region. Health professionals at the hospital and attached College of Nursing have considerable human capacity and willingness to undertake health research. However they are constrained by limited research experience, training opportunities, research systems, physical infrastructure and access to resources. This brief commentary describes an 'Introduction to Health Research' workshop delivered at Atoifi Adventist Hospital in September 2009 and efforts to move from 'research workshop' to 'research work'. The Approach Using a participatory-action research approach underpinned by decolonising methodologies, staff from Atoifi Adventist Hospital and James Cook University (Queensland, Australia) collaboratively designed, implemented and evaluated a health research workshop. Basic health research principles and methods were presented using active learning methodologies. Following the workshop, Atoifi Adventist Hospital and Atoifi College of Nursing staff, other professionals and community members reported an increased awareness and understanding of health research. The formation of a local Research Committee, improved ethics review procedures and the identification of local research mentors followed the week long workshop. The workshop has acted as a catalyst for research activity, increasing structural and human resource capacity for local health professionals and community leaders to engage in research. Discussion and Conclusions Participants from a variety of educational backgrounds participated in, and received benefit from, a responsive, culturally and linguistically accessible health research workshop. Improving health research systems at a remote hospital and aligning these with local and national research agendas is establishing a base to strengthen public health research and practice on Malaita, Solomon Islands.